PEMBEBASAN UTANG PAJAK DALAM RANGKA PENGAMPUNAN PAJAK - Astuti, Dwi Widia (JURNAL MEDIA HUKUM DAN PERADILAN, 2018)
The role of taxes is very important in the state finances. Taxes become necessary in financing the expenditures of the state, especially the routine state expenditures. However, not infrequently there are taxpayer actions that cause in State losses. The condition is realized by the government so that the government issued Law Number 11 Year 2016 on Tax Amnesty. However, with the issuance of the Tax Forgiveness Law, it has resulted in various views in the community because for some obedient taxpayers, it is assumed that taxpayers are granted the convenience of their mistakes. So that does not reflect justice as one of the objectives of the law. Based on the issue, the authors will conduct further research on the legality of tax debt relief in the framework of tax forgiveness and the urgency of determining the tax forgiveness rule. This study is qualified as a normative juridical legal research with a type of legal research doctrinal using a statutory approach, and a conceptual approach. From this research, it is expected that the writer can analyze related to the legality of tax debt relief in the framework of tax forgiveness and the urgency of determining tax forgiveness rule.